An investigations on local and global behavior of a (SMA) oscillator of 3 - DOF driven by a limited power supply - Piccirillo, Vinícius; Goes, Luiz Carlos Sandoval; Balthazar, José Manoel [UNESP] (ASME International, 2010)
SMART material systems offer great possibilities in terms of providing novel and economical solutions to engineering problems. The technological advantages of these materials over traditional ones are due to their unique microstructure and molecular properties. Smart materials such as shape memory alloys (SMA), has been used in such diverse areas of engineering science, nowadays. In this paper, we present a numerical investigation of the dynamics interaction of a nonideal structure (NIS). We analyze the phenomenon of the passage through resonance region in the steady state processes. We remarked that this kind of problem can lead to the so-called Sommerfeld effect: steady state frequencies of the DC motor will usually increase as more power (voltage) is given to it in a step-by-step fashion. When a resonance condition with the structure it is reached, the better part of this energy it is consumed to generate large amplitude vibrations of the foundation without sensible change of the motor frequency as before. The results obtained by using numerical simulations are discussed in details. Copyright © 2009 by ASME.
Keywords: Engineering problems; Engineering science; Global behaviors; Large amplitude vibrations; Limited power supply; Molecular properties; Nonideal structures; Numerical investigations; Numerical simulation; Resonance condition; Resonance region; Shape memory alloy; Smart material systems; Smart materials; Sommerfeld effect; Steady state; Steady state process; Step-by-step; Computer simulation; DC motors; DC power transmission; Engineering; Intelligent materials; Materials properties; Resonance; Structural design